2008
DOI: 10.1068/p5877
|View full text |Cite
|
Sign up to set email alerts
|

Top — Down Control of Visual Perception: Attention in Natural Vision

Abstract: IntroductionPre-emptive perception can be used to describe a situation in which a motor command influences perception. An example might be a command for a saccadic eye movement, in which a corollary discharge cancels the changed sensory input produced by the movement of the eyes, contributing to stability of visual perception (Wurtz and Sommer 2004). Here, I consider a somewhat different situation in which prior expectations influence visual perception. These prior expectations might consist of top^down attent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 62 publications
0
23
0
Order By: Relevance
“…One such property is that certain objects may need to be treated as similar for the correct performance of a task, and others as different, and that demand can influence the representations of objects in a number of brain areas (Fenske et al, 2006; Freedman and Miller, 2008; Kourtzi and Connor, 2011). That process may in turn influence representations in the inferior temporal visual cortex, for example, by top-down bias (Rolls and Deco, 2002; Rolls, 2008b,c). …”
Section: Invariant Representations Of Faces and Objects In The Inferimentioning
confidence: 99%
“…One such property is that certain objects may need to be treated as similar for the correct performance of a task, and others as different, and that demand can influence the representations of objects in a number of brain areas (Fenske et al, 2006; Freedman and Miller, 2008; Kourtzi and Connor, 2011). That process may in turn influence representations in the inferior temporal visual cortex, for example, by top-down bias (Rolls and Deco, 2002; Rolls, 2008b,c). …”
Section: Invariant Representations Of Faces and Objects In The Inferimentioning
confidence: 99%
“…Gottfried and Dolan (2003) noted higher activation of the OFC when a smell is presented with a word label [7]. Cognitive factors, such as visual stimuli modulate representations of odor at a relatively early level of cortical processing, known as the top-down cognitive influence, which directly affects emotion [38]. Healthy participants exhibited dominance of the visual sense in this study.…”
Section: Figure 6 (A) Strength Of the Odor Represented On The Visualmentioning
confidence: 63%
“…In the field of vision it has been observed that a specific blindness occurs for those changes in the visual field one does not pay attention to. This is referred to as inattentional blindness and is related to a lower activity of neurons which represent the objects one is not focussed on (see Rolls (2008) for a short overview). In the field of taste and smell it has been suggested that a small ''warm up" can increase participants' performance in a similarity test.…”
Section: Discussionmentioning
confidence: 99%